Catatan hitam lima presiden Indonesia : sebuah investigasi 1997-2007, mafia ekonomi, dan jalan baru membangun Indonesia - Rafick, Ishak, 1961- (Pasar Minggu, Jakarta, Indonesia : Ufuk Pub. House, 2008)
Politics and government and economic conditions in Indonesia during the administration of Suharto up to now.
Includes bibliographical references (p. 418-422).
Keywords: Indonesia -- Politics and government -- 1966-1998.; Indonesia -- Economic conditions -- 1966-1997.; Indonesia -- Politics and government -- 1998-; Indonesia -- Economic conditions -- 1997-